A prospective study on maternal near-miss and maternal mortality in a tertiary care hospital - Agrawal, Shubhangi; Thobbi, Vidya A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Maternal near-miss (MNM) has become a key indicator of healthcare quality, offering valuable insights into severe maternal morbidity. In developing countries, maternal morbidity remains a pressing issue, and understanding MNM cases is crucial for improving maternal health outcomes. The present study was carried out to evaluate the causes, interventions, and delays in managing maternal near-miss cases in a tertiary care hospital. Methods: This observational study was conducted at Al-Ameen Medical College and Hospital, from September 2022 to September 2023. A total of 863 deliveries were analyzed, and 67 MNM cases were identified. The study included pregnant women who experienced severe maternal complications, and data on demographic, clinical, and intervention characteristics were collected. The incidence ratio, mortality index, and delay factors were also calculated. Results: The MNM incidence ratio was 78.7 per 1000 live births. The most common risk factors were preeclampsia (29.9%), antepartum hemorrhage (APH) (16.4%), eclampsia, and surgical site infections (13.4%). A majority of MNM cases required high dependency unit (HDU) admission (55.2%), and 13.4% underwent hysterectomy. Delays were most prominent at the patient level (46.3%), followed by referral side delays (38.8%). The study also found that women with severe anemia had lower gestational ages and a higher incidence of transfusion interventions. Conclusions: This study highlights the significant burden of MNM, particularly due to hypertensive disorders and hemorrhage. Delays in care, especially from the patient and referral sides, contribute to poor maternal outcomes. Early detection, effective interventions, and improved healthcare systems at all levels are crucial to reduce maternal morbidity.